The influence of inter-company linkages on company performance : the case of the Irish software industry - Shugurov, Vladimir (Trinity College (Dublin, Ireland). Trinity Business School, 2001)
This study was undertaken to examine the following research question: How and why do inter-company linkages influence company performance? Many studies (e.g. Teece, 1997; Gemser, 1996; Hagedoom, 1990) have contributed conceptually to our understanding of inter-company linkages. However, none of them provides a completely appropriate answer to the research question. In the light of this, a new model has been developed, building primarily on dynamic models outlined in the literature review. This model attempts to explain the influence of inter-company linkages on company performance. Within this theoretical framework, linkages are understood to be joint R&D, production and marketing activities of two companies that require the combination of different resources in order to produce innovation for the use of either or both partners. The model processes two inputs, namely information about the types of inter-company linkages that companies have and the stage of development of the industry in which these companies operate into a single output - appropriateness of inter-company linkages.
Keywords: Business, Ph.D.; Ph.D. Trinity College Dublin